Tethering Cells via Enzymatic Oxidative Crosslinking Enables Mechanotransduction in Non‐Cell‐Adhesive Materials. Issue 42 (3rd September 2021) - Kamperman, Tom; Henke, Sieger; Crispim, João F.; Willemen, Niels G. A.; Dijkstra, Pieter J.; Lee, Wooje; Offerhaus, Herman L.; Neubauer, Martin; Smink, Alexandra M.; de Vos, Paul; de Haan, Bart J.; Karperien, Marcel; et al.
Abstract: Cell–matrix interactions govern cell behavior and tissue function by facilitating transduction of biomechanical cues. Engineered tissues often incorporate these interactions by employing cell‐adhesive materials. However, using constitutively active cell‐adhesive materials impedes control over cell fate and elicits inflammatory responses upon implantation. Here, an alternative cell–material interaction strategy that provides mechanotransducive properties via discrete inducible on‐cell crosslinking (DOCKING) of materials, including those that are inherently non‐cell‐adhesive, is introduced. Specifically, tyramine‐functionalized materials are tethered to tyrosines that are naturally present in extracellular protein domains via enzyme‐mediated oxidative crosslinking. Temporal control over the stiffness of on‐cell tethered 3D microniches reveals that DOCKING uniquely enables lineage programming of stem cells by targeting adhesome‐related mechanotransduction pathways acting independently of cell volume changes and spreading. In short, DOCKING represents a bioinspired and cytocompatible cell‐tethering strategy that offers new routes to study and engineer cell–material interactions, thereby advancing applications ranging from drug delivery, to cell‐based therapy, and cultured meat. Abstract : Cells need to sense their environment in order to survive and function. In this study an enzymatic crosslinking strategy that can tether non‐cell‐adhesive materials to cells is presented. By targeting the cellular adhesome, this cell–material tethering method enables cell‐volume‐independent lineage programming of stem cells in engineered 3D microniches with controlled stiffness.